2008
DOI: 10.1016/j.virol.2008.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Antibodies play a greater role than immune cells in heterologous protection against secondary dengue virus infection in a mouse model

Abstract: The four serotypes of dengue virus (DENV1-4) are causative agents of dengue fever and dengue hemorrhagic fever/dengue shock syndrome (DHF/DSS). Previous DENV infection is a risk factor for DHF/DSS during subsequent infection by a different serotype. Nonetheless, most primary and secondary DENV infections are asymptomatic. To investigate the possible mechanisms of immune protection in vivo, 129/Pas mice lacking IFN-α/β and -γ receptors (AG129) were used to model secondary infection using both DENV1-DENV2 and DE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
65
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(68 citation statements)
references
References 51 publications
3
65
0
Order By: Relevance
“…Whereas neutralizing antibody clearly protects against a homologous serotype (157, 175), controversy has centered on what function gives heterologous serotype protec-tion in the face of the enhanced disease that occurs in the presence of antibody-dependent enhancement (ADE) (57). It appears from studies in a mouse model that heterotypic neutralizing antibodies do give heterotypic protection if they are present in concentrations sufficient to protect but insufficient to cause ADE (8,78,186).…”
Section: Viruses Transmitted By Arthropodsmentioning
confidence: 99%
“…Whereas neutralizing antibody clearly protects against a homologous serotype (157, 175), controversy has centered on what function gives heterologous serotype protec-tion in the face of the enhanced disease that occurs in the presence of antibody-dependent enhancement (ADE) (57). It appears from studies in a mouse model that heterotypic neutralizing antibodies do give heterotypic protection if they are present in concentrations sufficient to protect but insufficient to cause ADE (8,78,186).…”
Section: Viruses Transmitted By Arthropodsmentioning
confidence: 99%
“…Sequential heterotypic DENV infection failed to induce enhanced viral load or mortality in AG129 mice (Kyle et al, 2008). Cross-reactive memory B and T cells likely contribute to protection from disease progression in mice (Zompi et al, 2012), and currently there is no model that reproduces human DHF/DSS-like disease caused by sequential infection.…”
Section: A Passive Transfer Of Antibodies or Immune Complexesmentioning
confidence: 99%
“…We previously reported that a DENV-2 DNA vaccine consisting of prM and 80% E (aa 1 to 396) of DENV-2, followed by 20% E from the homologous JEV membrane-anchoring region, enhanced VLP secretion after intracellular expression and was able to generate high-titer antibodies in mice which persisted for more than 6 months (28,44). DENV-neutralizing antibodies directed against the E protein are thought to play a key role in protection against the disease, an idea supported directly by passive antibody transfer experiments in animal models and indirectly by epidemiological data from prospective studies in areas where dengue is endemic (45,46). However, the levels of antibody induction and protection for a dengue vaccine have not been established under conditions of different antigenic backbones, and these might differ depending on the phylogenetic genotype differences.…”
Section: Discussionmentioning
confidence: 99%